Sea Level Interannual Variability Along the West Coast of India. Issue 22 (29th November 2018) - Suresh, I.; Vialard, J.; Lengaigne, M.; Izumo, T.; Parvathi, V.; Muraleedharan, P. M.
Abstract: Interannual sea level anomalies (SLA), and the related thermocline variations, along the west coast of India (WCI) strongly impact the ecosystems, fisheries, and potentially the monsoon rainfall. Here we investigate the mechanisms driving the WCI interannual SLA using a linear continuously stratified ocean model, which realistically simulates the leading northern Indian Ocean SLA mode associated with the Indian Ocean Dipole (IOD). During, for example, positive IOD events, easterly wind anomalies near Sri Lanka in late summer and fall force downwelling coastal Kelvin waves, which induce positive WCI SLA within days. Meanwhile, equatorial easterlies force upwelling Kelvin waves that travel to WCI through the Bay of Bengal coastal waveguide. Part of this opposite signal also transits slowly through the Bay of Bengal interior as Rossby waves, eventually yielding negative SLA along the WCI in winter. The WCI SLA thus shifts from positive in fall to negative in winter during positive IOD events. Plain Language Summary: The Indian Ocean Dipole (IOD) is the leading mode of Indian Ocean climate variability and is associated with anomalous winds over the equatorial Indian Ocean. A recent work has demonstrated that IOD events could strengthen or inhibit the upwelling of poorly oxygenated waters along the west coast of India (WCI). Such an upwelling impacts oxygen distribution in the upper layers and can thus have adverse effects on ecosystem and fisheries. Here we explain the mechanisms linking the IOD to upwelling along the WCI. IOD zonal winds in the central equatorial Indian Ocean produce two opposite signals on WCI. One that travels fast, directly up the WCI during summer and fall. But another opposite‐polarity signal follows equator and Bay of Bengal rim—a part of which transits slowly through the Bay of Bengal interior, eventually reaching the WCI and flipping the sign of sea level anomalies there in winter. Key Points: Positive Indian Ocean Dipoles induce positive (negative) sea level anomalies in boreal fall (winter) along the west coast of India Fall easterly wind anomalies near Sri Lanka force downwelling coastal Kelvin waves that travel quickly to the west coast of India Fall eastern equatorial upwelling signals travel more slowly through the interior Bay of Bengal, reaching the Indian west coast in winter